Best uniform approximation of a continuous compact-valued mapping by sets of continuous single-valued mappings - Hudyma, U. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We prove existence theorems and establish necessary and sufficient conditions and criteria for an extremal element for the problem of the best uniform approximation of a continuous compact-valued mapping by sets of continuous single-valued mappings.